2023
DOI: 10.1108/bfj-05-2022-0434
|View full text |Cite
|
Sign up to set email alerts
|

Branding Creative Cities of Gastronomy: the role of brand experience and the influence of tourists' self-congruity and self-expansion

Abstract: PurposeThis study explores the brand management and marketing of Creative Cities of Gastronomy. A framework based on brand experience was constructed to investigate its relationship with tourists' brand attachment and brand identification. Two factors that enable tourists to have a stronger brand experience from the self-concept perspective – self-congruity and self-expansion – were also examined.Design/methodology/approachThe authors adopted a quantitative research design and collected data from participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…The results indicate that there was a strong association between the sensory dimension and positive memory and that cognitive and affective dimensions partially mediate the relationship. Other theories applied by the reviewed literature include trust formation theory and social exchange theory (Torres-Moraga & Barra, 2023), self-expansion (Guo & Hsu, 2023), flow theory (Fu et al, 2020) and interactionist-based theory (Shang et al, 2020).…”
Section: Theories Used By Brand Experience Studies In the Tourism Ind...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicate that there was a strong association between the sensory dimension and positive memory and that cognitive and affective dimensions partially mediate the relationship. Other theories applied by the reviewed literature include trust formation theory and social exchange theory (Torres-Moraga & Barra, 2023), self-expansion (Guo & Hsu, 2023), flow theory (Fu et al, 2020) and interactionist-based theory (Shang et al, 2020).…”
Section: Theories Used By Brand Experience Studies In the Tourism Ind...mentioning
confidence: 99%
“…Other scholars such as Kim et al (2022), also examined the influence of destination brand and brand awareness on destination brand experience and found that both the destination brand and brand awareness are the predictors of destination branding. A study by Guo and Hsu (2023) in China utilized the self-congruity theory among others to determine the relationship between brand experience, selfcongruity, brand attachment, self-expansion and brand identification and found that self-congruity is an antecedent of brand experience. Interestingly, Rezaei et al (2017) in Iran, studied the influence of customer perceived relationship marketing, quality of service and brand experience on tourists' satisfaction and actual expenditure behavior.…”
Section: Antecedents Of Brand Experiencementioning
confidence: 99%
See 1 more Smart Citation